A Hybrid Troposkein Wind Turbine with Piezoelectric Energy Harvesting Patches and Solar Panels : Design and Performance Evaluations - Naveen Dhandapani; Karthik Arul; Ganapathy Kalyanasundaram; Laxana Sourirajan; Beena Stanislaus Arputharaj; Qasem M. Al-Mdallal; Mohammad Mukhtar Alam; Balaji Ganesan; Vijayanandh Raja (Ain Shams Engineering Journal)
The Troposkein wind turbine (TWT) is analyzed and developed from its inception. Classic aerofoils are investigated for wind turbines because of their low sensitivity to Reynolds Number. This study aims to determine the most efficient design for a TWT by adjusting the blade profile, number of blades, and aerofoils. Three comprehensive investigations have demonstrated that aerofoils based on the National Advisory Committee for Aeronautics (NACA)-633108 have a higher energy extraction capacity compared to other surfaces. In addition to these enhancements, the “Hybrid Concept” utilizes piezo-electric patches and solar panels to enhance the generation of electricity from TWT. The TWT model requires the use of substantial hybrid energy extraction procedures for energy results with an average power of 2 kW. The hybrid energy extraction functions are structurally facilitated by the combination of S-glass fibre composite and GY-70-based carbon fibre composite. Therefore, the utilization of hybrid energy extraction renders TWT a highly effective energy harvester.